A checklist of the ticks of Malaysia (Acari: Argasidae, Ixodidae), with lists of known associated hosts, geographical distribution, type localities, human infestations and pathogens - Kazim, Abdul-Rahman; Houssaini, Jamal; Tappe, Dennis; Heo, Chong Chin (Zootaxa, 2022)
Studies of ticks in Malaysia from past articles were reviewed, resulting in a list of 47 species belonging to seven genera (Argas, Ornithodoros, Amblyomma, Dermacentor, Haemaphysalis, Ixodes, and Rhipicephalus). The most prevalent genus in Malaysia is Haemaphysalis (20 species), followed by Amblyomma (eight species) and Dermacentor (seven species). Out of 47 species, only 28 have bitten humans, mostly belonging to Haemaphysalis. The most researched tick-borne pathogens in Malaysia are Rickettsia and Anaplasma, and most research was focused on the tropical-lineage brown dog ticks, R. sanguineus sensu lato, and the cattle ticks, Haemaphysalis bispinosa and Rhipicephalus microplus. 18 species were excluded from the list due to lack of definite records or dubious findings: Ornithodoros mimon, O. turicata, Amblyomma breviscutatum, A. clypeolatum, A. integrum, A. maculatum, Dermacentor marginatum, D. taiwanensis, Haemaphysalis birmaniae, H. flava, H. humerosa, H. longicornis, H. punctata, H. sulcata, Ixodes holocyclus, Rhipicephalus appendiculatus, R. annulatus and R. bursa. This paper presents the first complete and updated list for Dermacentor and Ixodes tick species in Malaysia since Kohls (1957).